Hubungan Sikap Ibu Usia Remaja dengan Perkembangan Emosional Anak Prasekolah (3-5 Tahun) Di Desa Tempeh Kidul Lumajang - Ulfa, Maria; Nur Endah Sari, Yessy; Ermawati, Iit (NHM PRESS, 2023)
Preschool-age children are the golden period. The quality of child development greatly determines the good future of children. One of the most important child development is emotional development. The purpose of this study was to determine the correlation between the attitude of adolescent mothers and the emotional development of preschool children (3-5 years) in Tempeh Kidul Village, Tempeh, Lumajang. The cross-sectional study design was used on 46 teenage mothers in Tempeh Kidul Village. Respondent characteristic questionnaire and adolescent mother attitude questionnaire and mental emotional problems questionnaire (KMME) chi-square test were used to answer the objectives of this study. The results showed that 28 respondents (60.9%) had a good attitude toward educating their children. The majority of the appropriate emotional development of preschool-age children was 28 respondents (60.9%). There is a significant relationship between the attitudes of adolescent mothers and emotional development of preschool children (3-5 Years) in Tempeh Kidul Village, Tempeh, Lumajang, namely p-value 0.0001. The suggests for teenage mothers should spend more time educating and caring for their children properly so that incidents of deviations in children's emotional development can be prevented as early as possible.